Stability in the leaf functional traits of understory herbaceous species after 12-yr of nitrogen addition in temperate larch plantations - Yan, Tao; Wang, Liying; Wang, Peilin; Zhong, Tianyu (Frontiers in Plant Science, 2023)
Leaf functional traits play critical roles in plant functioning. Although the functional traits of overstory trees have been extensively studied, minimal research has been conducted regarding understory species, despite the understory layer is an important component of temperate forests. Such insufficiency limit the broader understanding of processes and functions in forest ecosystems, particularly when under the increasing atmospheric nitrogen (N) deposition. Here, we investigated the responses of 18 leaf functional traits in six understory herbaceous species within young and mature stands (three species per stand) in larch (Larix principis-rupprechtii) plantations that subjected to 12 years of anthropogenic N addition. We found that N addition did not significantly impact the photosynthetic traits of understory herbaceous species in either stand; it only led to increased chlorophyll content in Geum aleppicum Jacq.Similarly, with the exception of decreases in the predawn leaf water potential of Sanguisorba officinalis L., N addition did not significantly affect leaf hydraulic traits.Ser. (decreased) and G. aleppicum (increased), N addition had negligible effects on leaf anatomical traits and specific leaf area, however, interspecific variations in the plasticity of leaf anatomical traits were observed. Stable responses to N addition were also observed for nonstructural carbohydrates (NSC) and their components (soluble sugars and starch), with the exception of Polygonum divaricatum L., which exhibited increases in NSC. Overall, our results suggest that the functional traits of understory herbaceous species exhibit stability under conditions of long-term N enrichment in leaf 删除[USER]: ecosystem 删除[USER]: subject to 删除[USER]: nonstructural carbohydrates 删除[USER]: temperate plantations.